2020
DOI: 10.1099/mgen.0.000458
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics reveals the toxin–antitoxin repertoire and AbiE activity in Serratia

Abstract: Bacteriophage defences are divided into innate and adaptive systems. Serratia sp. ATCC 39006 has three CRISPR-Cas adaptive immune systems, but its innate immune repertoire is unknown. Here, we re-sequenced and annotated the Serratia genome and predicted its toxin–antitoxin (TA) systems. TA systems can provide innate phage defence through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Recently, a new counter-defence mechanism against CRISPR/Cas has been uncovered, where phage T4 restores the broken genomic material, thereby making progeny phages resistant against future CRISPR attacks [36]. For those interested in more detailed information on anti-phage systems and the phage-bacteria arms race, we refer to some excellent recent reviews [31,35,37,38].…”
Section: Bacterial Defence Mechanisms Against Phagesmentioning
confidence: 99%
“…Recently, a new counter-defence mechanism against CRISPR/Cas has been uncovered, where phage T4 restores the broken genomic material, thereby making progeny phages resistant against future CRISPR attacks [36]. For those interested in more detailed information on anti-phage systems and the phage-bacteria arms race, we refer to some excellent recent reviews [31,35,37,38].…”
Section: Bacterial Defence Mechanisms Against Phagesmentioning
confidence: 99%
“…Recently it was demonstrated that AbiEii homo logue MenT 3 from Mycobacterium tuberculosis can trans fer pyrimidines to the acceptor stem of the specific tRNAs [137]. In agreement with this is the fact that over expression of AbiE toxin in Serratia causes growth cessa tion and decrease in the tRNAs levels [138]. In E. coli, the Type II system MazEF interferes with phage P1 propaga tion [139], and the Type I TA system hok/sok reduces the burst size of T4 phage [140].…”
Section: Induced Cell Dormancy or Suicide -Abortive Infection (Abi) And Toxin-antitoxin (Ta) Systemsmentioning
confidence: 83%
“…ATCC39006 strain LacA (hereafter Serratia ) ( 24 , 25 ). This Serratia strain is an environmental isolate that encodes type I-E, I-F and III-A CRISPR-Cas systems, in addition to multiple toxin-antitoxin and other defence systems ( 22 , 26 ). Using SorTn-seq, we identified and characterised an Rcs stress response pathway that inversely controls CRISPR-Cas and surface immunity.…”
Section: Introductionmentioning
confidence: 99%